2017
DOI: 10.2217/pme-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

LEPR Gene Polymorphism and Plasma Soluble Leptin Receptor Levels are Associated with Polycystic Ovary Syndrome in Han Chinese Women

Abstract: Aim:To investigate the association of LEPR polymorphisms and plasma leptin and soluble leptin receptor (sOB-R) levels with polycystic ovary syndrome (PCOS) in Chinese women. Patients & methods: LEPR Lys109Arg (rs1137100) and Gln223Arg (rs1137101) polymorphisms of PCOS patients and the controls were genotyped. Plasma leptin and sOB-R levels of two groups were measured. Results: The genotypic distributions of Lys109Arg (rs1137100) differed between the PCOS and control groups. Plasma sOB-R levels increased signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…() found SNPs in the coding region of the LEPR gene that were strongly correlated with age at onset of puberty in sheep. Moreover, one new study has also shown that polymorphisms of LEPR are correlated with polycystic ovary syndrome in Han Chinese women (Tu et al, ). The multifarious effects of the LEPR mutations on reproductive traits highlight the crucial role of leptin in regulating reproductive efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…() found SNPs in the coding region of the LEPR gene that were strongly correlated with age at onset of puberty in sheep. Moreover, one new study has also shown that polymorphisms of LEPR are correlated with polycystic ovary syndrome in Han Chinese women (Tu et al, ). The multifarious effects of the LEPR mutations on reproductive traits highlight the crucial role of leptin in regulating reproductive efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A first study including 229 PCOS patients and 150 controls reported a highly significant association of Gln223Arg SNP in the LEPR gene with the development of PCOS ( p < 0.0001) [ 129 ]. A subsequent study on 326 PCOS patients and 283 control individuals reported homozygous genotypes of LEPR SNP Lys109Arg (rs1137100) to be associated with PCOS ( p = 0.012) [ 130 ]. A recent meta-analysis conducted on 33 studies identified a significant association of LEPR rs1137101 polymorphism with the susceptibility to PCOS in a recessive genetic model ( p = 0.002, OR 1.88, 95% CI 1.26–2.78) [ 131 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…As shown in Table 5 The association of LEPR gene with pathologies, including obesity [20], diabetes [17,22], pregnancy complications [29,30], cancer [31,32] was investigated in several populations. Few studies on Caucasian and Asian populations examined the association of LEPR genetic variants with PCOS, but with inconclusive findings, and an ethnic contribution to this association was suggested.…”
Section: Resultsmentioning
confidence: 99%